2016
DOI: 10.1086/688666
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Selection and Local Adaptation Jointly Shape Life-History Evolution during Range Expansion

Abstract: In the context of climate change and species invasions, range shifts increasingly gain attention because the rates at which they occur in the Anthropocene induce rapid changes in biological assemblages. During range shifts, species experience multiple selection pressures. For poleward expansions in particular, it is difficult to interpret observed evolutionary dynamics because of the joint action of evolutionary processes related to spatial selection and to adaptation toward local climatic conditions. To disen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…Generally, dispersal and aggressiveness or boldness appeared to be coupled at range expansion fronts (Cote and Clobert 2007, Duckworth and Badyaev 2007, Cote et al 2010, Korsten et al 2013. However, and in line with earlier described expectations, a study combining quantitative genetics and inverse modelling demonstrated that dispersal and life history traits independently evolve according to respectively spatial sorting and local environmental conditions (Van Petegem et al 2016). It remains however to be studied to which degree evolved changes at range borders effectively affect ecological dynamics since environmental and demographic conditions may be highly different.…”
Section: A B D Csupporting
confidence: 67%
“…Generally, dispersal and aggressiveness or boldness appeared to be coupled at range expansion fronts (Cote and Clobert 2007, Duckworth and Badyaev 2007, Cote et al 2010, Korsten et al 2013. However, and in line with earlier described expectations, a study combining quantitative genetics and inverse modelling demonstrated that dispersal and life history traits independently evolve according to respectively spatial sorting and local environmental conditions (Van Petegem et al 2016). It remains however to be studied to which degree evolved changes at range borders effectively affect ecological dynamics since environmental and demographic conditions may be highly different.…”
Section: A B D Csupporting
confidence: 67%
“…Lab experiments also demonstrate dispersal evolution during range expansion and suggest evolution of dispersal and population growth rate can occur in three to four generations under idealized lab conditions (Fronhofer and Altermatt 2015, Williams et al 2016, Ochocki and Miller 2017, SzƱcs et al 2017, Weiss-Lehman et al 2017, Van Petegem et al 2018). Furthermore, dispersal evolution has been observed during range expansions in natural systems for invasive species (Phillips et al 2010b, Lombaert et al 2014, Van Petegem et al 2016) and for species responding to climate change (Hill et al 1999, Simmons and Thomas 2004. Taken together, evidence suggests that dispersal evolution could accelerate climate-induced range expansions for many species vulnerable to climate change.…”
Section: Cool Range Marginsmentioning
confidence: 96%
“…Individual-based models show for instance that dispersal evolution during range expansion can be constrained by investments in competitive abilities, reproduction (Burton et al 2010) and thermal adaptations (Hillaert et al 2015). In absence of genetic correlations, dispersal and life history traits independently evolve according to respectively spatial sorting and local environmental conditions (Van Petegem et al 2016). It remains thus to be studied to which degree evolved changes at range borders effectively affect ecological dynamics since environmental and demographic conditions may be highly different.…”
Section: Consequences -Genetic (Co-)variationmentioning
confidence: 99%